Study of rat hypothalamic proteome by HPLC/ESI ion trap and HPLC/ESI‐Q‐TOF MS. Issue 16 (17th July 2013) - Iqbal, Javed; Li, Wang; Ullah, Kaleem; Hasan, Murtaza; Linna, Guo; Awan, Umer; Zhang, Yongqian; Batool, Sajida; Qing, Hong; Deng, Yulin
<x xml:space="preserve">Abstract</x> The proteomic profile of hypothalamus, a key organ of CNS, is explored here by employing two widely used MS techniques, i.e. HPLC/ESI‐ion trap and HPLC/ESI‐quadrupole‐TOF MS. Strong cation exchange is used for the fractionation of peptides and protein search engine MASCOT is employed for data query. One hundred and thirty six proteins with 10 973 peptides were identified by HPLC/ESI‐ion trap MS, while 140 proteins with 32 183 peptides were characterized by HPLC/ESI‐quadrupole‐TOF MS. Among the total 198 proteins identified in both experiments, 78 proteins were common in both sets of conditions. The rest of the 120 proteins were identified distinctly in both MS strategies, i.e. 58 unique proteins were found using the quadrupole‐TOF while 62 were found with the HPLC/ESI‐ion trap. Moreover, these proteins were classified into groups based on their functions performed in the body. Results presented here identified some important signal and cellular defense proteins inevitable for survival in stressed conditions. Additionally, it is also shown that any single MS strategy is not reliable for good results due to loss of data depending on sensitivity of the instrument used.